2016
DOI: 10.1111/jce.13128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Left Atrial Transport Function in Patients Who Maintained Sinus Rhythm After Successful Radiofrequency Catheter Ablation for Atrial Fibrillation: A 1‐Year Follow‐Up Multislice Computed Tomography Study

Abstract: Although SR was maintained for 1 year after AF ablation, LAEF as well as LAV decreased. The extent of LAEF deterioration was significantly associated with the amount of iatrogenic myocardial damage. Our data indicate that extensive atrial ablation may lead to LA functional deterioration, especially in patients with PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…It is noteworthy that two‐dimensional echocardiography, RT3DE, computed tomography and cardiac magnetic resonance have all been utilized in studies for this purpose. LAEF preservation, deterioration or improvement in distinct subgroups (based on baseline atrial function or on AFib recurrence) after pulmonary vein isolation have been reported. The intrinsic dissimilarities of different imaging approaches along with potential methodological issues (for instance, heart rhythm at the time of measurement acquisition) may be responsible for the contradictory findings .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that two‐dimensional echocardiography, RT3DE, computed tomography and cardiac magnetic resonance have all been utilized in studies for this purpose. LAEF preservation, deterioration or improvement in distinct subgroups (based on baseline atrial function or on AFib recurrence) after pulmonary vein isolation have been reported. The intrinsic dissimilarities of different imaging approaches along with potential methodological issues (for instance, heart rhythm at the time of measurement acquisition) may be responsible for the contradictory findings .…”
Section: Discussionmentioning
confidence: 99%
“…AF can lead to reversible chamber dilatation and dysfunction of LA with the extent of rate-related cardiomyopathy (1). Shrinkage of the large LA chamber may occur in patients who undergo catheter ablation of AF, and it has been defined as a reverse remodeling of left atrium (19,20). This remodeling may be due to the decreased burden of AF and scar formation from the catheter ablation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Shrinkage of the large LA chamber may occur in patients who undergo catheter ablation of AF, and it has been defined as a reverse remodeling of left atrium (19,20). This remodeling may be due to the decreased burden of AF and scar formation from the catheter ablation (20). The degree of LA shrinkage strongly correlates with the extent of ablation-induced scarring in the LA wall after catheter ablation of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with healthy atria who typically have only paroxysmal AF, the consequences of the injury may be modest 23 . However, the procedure-related cardiomyocyte loss eventually leads to replacement fibrosis, and in patients with long-standing AF and severely diseased atria, ablation-induced injury can have serious deleterious effects on LA structure and function ( Take home figure ) 24 . The quantity of loss of contractile tissue and replacement fibrosis depends on the extent or number of procedures, but 30–35% of the LA wall may be replaced by scar following ablation 25 , 26 .…”
Section: Characterization Of Left Atrial Injury Induced By Catheter Amentioning
confidence: 99%
“…Ablation is followed by impairment of LA systolic function, which is related to the magnitude of scar formation 20 . During follow-up, 40–70% of patients who undergo ablation show a decrease in LA ejection fraction, particularly if they have demonstrated biochemical evidence of cardiomyocyte death (as reflected by CK-MB and troponin release); this is especially likely with extensive or multiple procedures 24 . In one-third of patients, restoration of electrocardiographic P waves is not accompanied by haemodynamic evidence of meaningful atrial systole, i.e.…”
Section: Consequences Of the Effect Of Ablation On Left Atrial Systolmentioning
confidence: 99%